Comparison of Diagnostic Yield and Safety between Semirigid Pleuroscopic Cryobiopsy and Forceps Biopsy for Undiagnosed Pleural Effusion - Chung-Shu Lee; Shih-Hong Li; Chih-Hao Chang; Fu-Tsai Chung; Li-Chung Chiu; Chun-Liang Chou; Chih-Wei Wang; Shu-Min Lin (Canadian Respiratory Journal)
For undiagnosed pleural effusion, diagnostic yields and safety were similar between pleuroscopic cryobiopsy and forceps biopsy, but cryobiopsy obtained a larger pleural tissue sample than forceps biopsy.